Comparative study of thermal performance indicators of five hollow bricks configurations - Alaoui Ahlam; Kadic Muamer; Guenneau Sébastien; Lahsaini Mohammed; Achaoui Younes (E3S Web of Conferences)
In every country on the globe, there are still actions to perform in order to improve buildings' energy efficiency, particularly in regions with severe weather conditions. Since walls are heat-dissipating elements in the building, designing them effectively can help reduce the energy consumption of the HVAC (heating, ventilation, and air-conditioning) systems, which are notorious for using excessive amounts of energy. The use of self-insulating construction materials with relatively high thermal resistance and low transmittance is the most effective approach to achieve universal thermal insulation in all buildings. In order to enhance the thermal performance of red clay bricks, the present study evaluates several design approaches. Five configurations are assessed, namely the case of conventional bricks, the use of aluminum shields, low thermal emissivity coating, extruded polystyrene and air cavity partitioning. Finite element method based analysis in steady-state and transient conditions enabled the assessment of the effects of each technique and their classification according to thermal performance level.